Barriers and strategies of using student social network (SHĀD) in the teaching and learning of students during the corona outbreak: A phenomenological study - Amir Morādi; Saee'd Zarghāmi hamrāh (فصلنامه نوآوری‌های آموزشی, 2021)
Virtual education and the possibility of holding the classroom in cyberspace is a unique opportunity to cope with limitations of face-to-face education, the realization of the ideal of education for all and paving the way for sustainable and balanced development in the country. The aim of this study was to analyze and understand the lived experience of teachers, students and parents from the barriers and strategies of using the social network of students (SHĀD) in teaching and learning of students during the corona outbreak, in the three districts of Kermānshāh city. For this purpose, using a qualitative method with a phenomenological approach, the phenomenon under study was identified and represented. The research sample consisted of 22 teachers, principals, students and parents who were active in the SHĀD system and they were selected using purposive sampling method. Data were collected through semi-structured in-depth interviews and they were analyzed based on the Colaizzi model. In the 14th interview, the theoretical saturation of the data was obtained, however, in order to validate the findings, interviews were continued until the 22th person. Analysis of the interview data led to the identification of two main categories (barriers and strategies) and twenty main themes. The barriers of the SHĀD application were identified as the two categories of "teachers and principals' understanding" and "students and parents' understanding". The results showed that the use of SHĀD application for students' teaching and learning still has many different barriers. It became clear that there is a long way to reach the desired situation and improving its quality requires the view of authorities and staying away from temporary, part-time, second-hand attitude towards such education.